A water productive and economically profitable paddy rice production method to adapt water scarcity in the Vu Gia-Thu Bon river basin, Vietnam - Nay-Htoon, Bhone; Tung Phong, Nguyen; Schlüter, Sabine; Janaiah, Aldas (JNRD - Journal of Natural Resources and Development, 2013)
In Vu Gia-Thu Bon river basin, Vietnam, drought during the dry season affected negatively on rice production. High and uneven rainfall distribution cause flooding in the basin during wet season and cause severe agricultural drought during dry season. This study aimed to point out a higher water productive and economically efficient rice production method to adapt water scarcity in the region. Based on available secondary data, water productivity is calculated for different water saving rice production methods, according to Pereira, et al, (2012)’s irrigation water productivity and total productivity equations. The profit of technological change is calculated by partial budget analysis of rice production in that area and a sensitivity analysis supports to point out which input factor is sensitive to farmer’s benefit. Farmer’s psychological and social beliefs are used to create fuzzy logic based decision making model. Although water productivities (ranging 0.441 kg/m3/ha to 0.504 kg/m3/ha) are ranked as the second after System of Rice Intensification, we demonstrated that Alternate Wetting and Drying method is a recommendable method to the farmer after considering economic profitability and technical simplicity. The System of Rice Intensification method also could be a suitable method to adopt because this method is the highest water productive method (Water Productivities are ranging from 0.77 kg/m3/ha to 1.02 kg/m3/ha) coupled with highest yield of rice, subject to certain ecosystem services and payment policies should be developed to subsidize the reduced benefit resulting from this method.